Pengelolaan Arsip Dalam Mendukung Pelayanan Informasi Pada Bagian Tata Usaha - Aditya Riza Putra; Muhamad Abdul Aziz; Ermita; Fifin Wildanah (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2025)
A good and maximum archive management system will provide optimal information services in the school administration section. This study aims to analyze and analyze the archive management system in supporting information services in the school administration section. The research method used is a qualitative approach with a literature review design, involving collecting and analyzing various academic sources, such as journals and indexed articles from Google Scholar, Scopus, and SINTA as well as other relevant documents. Data were collected through library literature and journals that are relevant to the study. The results of the study indicate that the archive management system will have a very large impact on information services in the school administration section in carrying out education management.